Distibution Analysis Of Skipjeck Katsuwonus Pelamis In Sinjai Regency (Case Study On Fish Landed Ppi Lappa In Sinjai Regency) - Budiyamin -; Suryawati Salam; Hadijah - (Postgraduate Bosowa University Publishing, 2018)
The distribution pattern of Skipjack in PPI/TPI Lappa through three patterns disribusi namely: Fisherman (producer) - Retailers - small traders – top consumers Fisherman (producer) - small traders – top consumer Fisherman (producer) - wholesaler – consumer. Amount of margin, profit and marketing efficiency of marketing agencies skipjack in TPI Lappa sequential as follows: Fishermen with margin Rp. 33,750/Kg, advantages Rp. 33,750/Kg and 0.53% efficiency, Small Traders with a margin of Rp. 4,250/Kg, a profit of Rp. 3,549/Kg and efficiency of 1.87% with a margin Wholesalers Rp. 10,000/kg, a profit of Rp. 9,249/Kg and 1.72% Efficiency Retailers with a margin of Rp3,750/Kg, profit Rp.3,379/Kg and efficiency of 0.99%. The need to conduct further research on the patterns of distribution marketing for kinds of fish landed in PPI Lappa so that the distribution pattern of fish landed marketing can be known thoroughly kinds of fish landed in PPI Lappa.